Virtual photons in the ground state of a dissipative system - Simone De Liberato (Nature Portfolio, 2017)
Phenomena linked with ultrastrong coupling rely on the presence of virtual photons in the system’s ground state. In this article, using exact diagonalization, De Liberato shows that the population of ground state virtual photons is only quantitatively affected by losses.